2022
DOI: 10.1016/j.acra.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Practice-Based Learning Using Smart Class: A Competency-Based Model in Undergraduate Radiology Education

Abstract: Rationale and Objectives: A need for adequate and early exposure to radiology practice is rising in undergraduate students, taking competency development as the orientation. We aimed to develop a competency-based model of practice-based learning for undergraduate radiology education. Materials and Methods:The model of practice-based learning was constructed upon an e-learning smart class environment, with casebased learning and simulators for competency development. To assess the model effectiveness, a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The experience of introducing a competency-based approach in the postgraduate training of medical residents in the People's Republic of China has been successful. Scientists Y. Qin et al [25] and Q. Chen et al [26] emphasized humanistic literacy, collegiality in decision-making, interpersonal communication, and professional ethics. However, in 2016, F. Zhou et al [8] cross-sectioned the results of this approach and identified previously unaccounted for shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of introducing a competency-based approach in the postgraduate training of medical residents in the People's Republic of China has been successful. Scientists Y. Qin et al [25] and Q. Chen et al [26] emphasized humanistic literacy, collegiality in decision-making, interpersonal communication, and professional ethics. However, in 2016, F. Zhou et al [8] cross-sectioned the results of this approach and identified previously unaccounted for shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed a model of technological practice-based learning that was constructed in a smart and efficient interaction environment of e-learning curricula, with case-based learning and simulators for competency development [19]. At the present stage, many universities developing competency-based education (CBE) programs and learning models in higher education for students and teachers are filling the gap between academic outcomes and industrial needs [20], and current techniques and contents of CBE can be used for the curricular design of faculty development programs for continuing professional development [21], especially for TPD.…”
Section: Competency-based Education and Competency-based Teacher Prof...mentioning
confidence: 99%
“…Students were more satisfied, with the average comprehensive assessment score of students who participated in the smart classroom teaching reform being 3.4 points higher than students in other parallel classes such as dentistry and public health. Yun Q et al (2020) [ 3 ] used a randomized controlled trial method for a junior medical student radiology course, with the experimental group using smart-class (the smart-class group) and the control group using the traditional teaching method, and found that the Smart-Class group had higher mean quiz scores (r = 0.4, p = 0.001) and final exam application scores (r = 0.3, p = 0.005) than the traditional group. Liu FY et al (2019) [ 4 ] analyzed and summarized 123 articles of smart classroom literature published in core journals from 2010 to 2018 on The China Knowledge Network Database, with 119 articles of smart class in social science, 18 articles in information technology, and 4 articles in philosophy and humanities, respectively, and a weak combination of smart class in medicine.…”
Section: Introductionmentioning
confidence: 99%